Perbaikan Fitur Dashboard Skripsi di FILKOM APPS dengan menggunakan Pendekatan Human Centered Design - Rifqi Fachrizal Rochman; Komang Candra Brata; Herman Tolle (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
FILKOM APPS is software with a web platform that is integrated with business processes running at the Faculty of Computer Science, Universitas Brawijaya. The features offered by the FILKOM application are quite diverse, one of which is a dashboard. A dashboard is a visualization of information by providing an interface in various forms such as diagrams, reports, visual indicators combined with dynamic and relevant information. Faculties of Computer Science are often faced with fast academic business processes, for example, the process of guiding students' thesis to lecturers is often faced with a lack of efficiency and effectiveness in presenting data. In this regard, it is necessary to carry out continuous monitoring and measurement of performance to ensure the achievement of the goals that have been set. Improvement of the design by adding monitoring features to the evaluation of performance and processes using the Human-Centered - Design method which aims to create an interactive system that is expected to be able to solve problems regarding the effectiveness and efficiency of data presentation. The results obtained from the evaluation of the design improvement using the System Usability Scale, the effectiveness level is 69%, the efficiency level is 94.5% and the questionnaire results are 74.5% that the user is satisfied with the additional feature improvement, namely monitoring.